The Acquisition of Sociolinguistic Competence in a Lingua Franca Context - Durham, Mercedes (Multilingual Matters, 2014)
In a world where an increasing amount of communication takes place in English among non-native speakers, this study presents data from email exchanges to provide the first examination of sociolinguistic competence and the acquisition of native-like variability in an English as a Lingua Franca (ELF) context. The analysis of a range of linguistic variables (future tense, relative pronoun choice, complementizer use and adverbial placement) in the online interactions of Swiss speakers (with German, French and Italian mother tongues) allows the reader to gain a greater understanding of which linguistic features are source language-related and which are learning-related. This book will be a valuable resource for postgraduates and researchers interested in language variation and change, ELF and second language acquisition, as well as for undergraduates wanting guidance on different ways of examining sociolinguistic variables
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: ELF.; English as a Lingua Franca; foreign language learning; Lingua Franca; linguistic variables; Second Language Acquisition; second language learning; SLA.; Sociolinguistic Competence; sociolinguistics; Interlanguage (Language learning); Language and languages -- Variation; Second language acquisition; Sociolinguistics -- Switzerland; Soziolinguistik; Sprachkompetenz; Englisch; Fremdsprachenlernen; Verkehrssprache